Apicidin Inhibited Proliferation and Invasion and Induced Apoptosis via Mitochondrial Pathway in Non-small Cell Lung Cancer GLC-82 Cells - Zhang, Jianye; Lai, Zhenzhu; Huang, Wenjing; Ling, Huiping; Lin, Minting; Tang, Sili; Liu, Yun; Tao, Yiwen (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Apicidin, as an inhibitor of histone deacetylase, showed a wide range of antiproliferative activity against various cancer cell lines. Apicidin has also been reported to induce apotosis via Fas/Fas ligand. Yet few studies have been focused on mitochondrial pathway for its anti-tumor activity. Objective: In this study, we evaluated its involved mitochondrial mechanism against non-small cell lung cancer GLC-82 cells. Method: Apicidin was isolated from the mangrove endophtic fungi Fusarium sp. by solvent extraction and column chromatography. Its structure was elucidated by MS and NMR spectroscopic data, and comparison of those data with published data. Furthermore, anti-tumor activity and mitochondrial pathway of apicidin against GLC-82 cells were studied. Results: Apicidin was obtained from secondary metabolites of Fusarium sp., and it showed potent inhibitory activity against GLC-82 cells with the IC50 value of 6.94 ± 0.27 µM. Furthermore, apicidin suppressed proliferation and invasion, and induced apoptosis via mitochondrial pathway in GLC-82 cells, including loss of ΔΨm, release of cytochrome c from mitochondria, activation of caspase-9 and -3, and cleavage of poly-ADP-ribose polymerase. Conclusion: Apicidin, an inhibitor of histone deacetylase obtained from the mangrove endophytic fungi Fusarium sp., not only inhibited proliferation and invasion of GLC-82 cells, but also induced apoptosis via the mitochondrial pathway.
Keywords: apoptosis